Global survey of alternative splicing and gene modules associated with fertility regulation in a thermosensitive genic male sterile wheat. (27th November 2021) - Bai, Jianfang; Wang, Yukun; Liu, Zihan; Guo, Haoyu; Zhang, Fengting; Guo, Liping; Yuan, Shaohua; Duan, Wenjing; Li, Yanmei; Tan, Zhaoguo; Zhao, Changping; Zhang, Liping
Abstract: Thermosensitive genic male sterile (TGMS) wheat lines are the core of two-line hybrid systems. Understanding the mechanism that regulates male sterility in TGMS wheat lines is helpful for promoting wheat breeding. Several studies have obtained information regarding the mechanisms associated with male sterility at the transcriptional level, but it is not clear how the post-transcriptional process of alternative splicing might contribute to controlling male sterility. In this study, we performed genome-wide analyses of alternative splicing during the meiosis stage in TGMS line BS366 using PacBio and RNA-Seq hybrid sequencing. Cytological observations indicated that cytoskeleton assembly in pollen cells, calcium deposition in pollen and tapetal cells, and vesicle transport in tapetal cells were deficient in BS366. According to our cytological findings, 49 differentially spliced genes were isolated. Moreover, 25 long non-coding RNA targets and three bHLH transcription factors were identified. Weighted gene co-expression network analysis detected four candidate differentially spliced genes that had strong co-relation with the seed setting percentage, which is the direct representation of male sterility in BS366. In this study, we obtained comprehensive data regarding the alternative splicing-mediated regulation of male sterility in TGMS wheat. The candidates identified may provide the molecular basis for an improved understanding of male sterility. Abstract : Comprehensive analysis of alternative splicing events and differentially spliced genes in a thermosensitive genic male sterile wheat line identifies fertility-related gene modules, lncRNAs, and transcription factors.